Suitability of elite genotypes for wet-direct seeding in rice-rice system in Vertisol - Saha, Soumya; Tuti, Mangal Deep; Kumar, R Mahender; ., Bandeppa; Singh, T Vidhan (ORYZA-An International Journal of Rice, 2020)
This study was conducted to evaluate few elite rice genotypes in wet-direct seeded system vis-à-vis conventional transplanting in clayey vertisol of Telangana during two consecutive seasons (rabi and kharif) of 2015-16. Theexperiment was laid out in split-plot design with two methods of crop establishment in main plots viz. conventional transplanting (CT) and direct seeded rice (DSR) in puddled condition with nine rice varieties of differentgrowth duration in sub-plots and replicated thrice. Growth and yield attributing characters were not differed in both the establishment techniques. Grain yields during the rabi season was higher by about 1.5 % under DSR, whereas, during kharif it was about 1 % higher in transplanted rice. Total duration of cultivars was decreased in DSR to the tune of 14 days during two seasons. There was no significant difference in mean grain yield across rice cultivars in two consecutive growing seasons between direct seeding and conventional transplanting.During rabi season DRR Dhan 44, Rasi, DRRH-2, HRI-174, RNR 15048, RP Bio-226 performed well; whereas Rasi, DRR Dhan 44, DRRH-2 and Varadhan found suitable in kharif.